Chloride ion: A promising hole scavenger for photocatalytic hydrogen generation. (5th April 2018) - Hippargi, Girivyankatesh; Mangrulkar, Priti; Chilkalwar, Anushree; Labhsetwar, Nitin; Rayalu, Sadhana
Abstract: The investigation pertains to elucidation of promising role of in-situ chloride ions generated during the photoreduction of HAuCl4 as an internal sacrificial donor for photocatalytic hydrogen generation. The hydrogen evolution rate (HER) observed was 4.16 mmol h −1 using in-situ route of photocatalyst formation which is significantly higher than the conventional route of formation of recovered photocatalyst. This unreported and unprecedented enhancement is explained on the basis of role of chloride ions released from the gold precursor. Experimental data inferring the effect of chloride ions on photocatalytic hydrogen generation using AuTiO2 are also briefly explained. The role of anionic sacrificial donors suggests several potential possibilities for their applications in photocatalysis considering their presence in wastewater as well as their low cost and abundant availability. The work also introduces one-step photodeposition and hydrogen generation process against traditional recovered photocatalyst, wherein the catalysts were prepared first by normal route of photodeposition, recovered and then employed for hydrogen generation. Graphical abstract: Fig. shows stepwise mechanism for the chloride ions released during photo-reduction with consequent implication on photocatalytic hydrogen generation reaction. Highlights: The investigation pertains to elucidation of promising role of chloride ion in photocatalytic hydrogen generation. The chloride ions generated during the photoreduction of HAuCl4 used as internal sacrificial donor. The results shows unprecedented enhancement in photocatalytic hydrogen generation. The work also introduces single step photodeposition and hydrogen evolution system.